2016
DOI: 10.3390/en9010039
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Channel Influence to Power Line Communications Based on ITU-T G.9904 (PRIME)

Abstract: ITU-T G.9904 standard, also known as PoweRline Intelligent Metering Evolution (PRIME), is a Power Line Communications standard for advanced metering, grid control and asset monitoring defined by the International Telecommunication Union (ITU). In this paper, an analysis about how different characteristics of the communication channel and types of noise might affect the system performance is carried out. This study is based on simulations of the PRIME physical layer using different channel characteristics and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 11 publications
2
16
0
Order By: Relevance
“…PRIME specification defines an optional convolutional encoder for certain modulation schemes. A previous study from the authors concluded that modulation schemes without convolutional encoder are not efficient for real field scenarios [10], an observation that is consistent with other studies [17,18].…”
Section: Prime: Reed-solomon Encodingsupporting
confidence: 87%
“…PRIME specification defines an optional convolutional encoder for certain modulation schemes. A previous study from the authors concluded that modulation schemes without convolutional encoder are not efficient for real field scenarios [10], an observation that is consistent with other studies [17,18].…”
Section: Prime: Reed-solomon Encodingsupporting
confidence: 87%
“…The electric power lines may be aerial (overhead), underground, or inside the walls, floors or ceilings of user premises. In-house PLC devices may establish closed networks within a user's premises or provide connections to Access PLC networks or both [20,23,26,27].…”
Section: B In-house Plcmentioning
confidence: 99%
“…Noise is usually composed of randomly occurring voltages, which are unrelated in phase or frequency. Interference on the other hand is usually more structured than noise since it arise as unwanted coupling from just a few signals in the network [12,23,48].…”
Section: A Noise and Interference In Power Line Communicationmentioning
confidence: 99%
See 1 more Smart Citation
“…According to [3], some tangible deliverables from smart grid initiatives include real-time pricing, demand response (DR), electric vehicle charging control, integration of distributed Furthermore, many smart grid applications require low data rate; hence, it is understandable that NPLC dominated previous discussions [9][10][11][12][13][14], and funded projects such as [15][16][17][18][19] in relation to smart grids and their applications in low voltage (LV) regions. Apart from electromagnetic compatibility (EMC) issues in PLC generally [20,21], other major arguments against BPLC have been that 2-30 MHz cannot traverse an medium voltage/low voltage (MV/LV) step-down transformer without external bypass coupling circuit and that it suffers from high attenuation with distance [6].…”
Section: Introductionmentioning
confidence: 99%